Lagu Dolanan ‘Suwe Ora Jamu’ sebagai Media Terapeutik dalam Kegiatan Belajar Mengajar Anak Autis di Sekolah Khusus Autisme Bina Anggita Yogyakarta - Kania Azzahra Dharmawan; Intansari Wahyuning Widiyasih; Ria Setiawan; Ary Nugraha Wijayanto (Institut Seni Indonesia Denpasar, 2022)
Purpose: The purpose of this study was to explain the types of gamelan and gendhing (songs) used and to describe the form of interaction response that occurred between respondents and the child's gendhing dolanan 'Suwe Ora Jamu' before and after being given a pre-session music therapy at the special school for autism Bina Anggita Yogyakarta. Research Methods: This study uses a qualitative method with the type of case study which is a research strategy by carefully investigating an event, program, activity, and process or a group of individuals. Results and discussion: The choice of case study as a research strategy design because the use of gamelan as a therapeutic medium is a program implemented by the Sekolah Luar Biasa Bina Anggita Yogyakarta in helping improve the condition of autistic children in teaching and learning activities. Implication: The results showed that the use of the children's play song 'Suwe Ora Jamu' gave different emotional responses to each student, both before and after being given a pre-therapy session.